Bilateral nerve conduction studies in the evaluation of distal symmetric polyneuropathy. Issue 3 (2nd July 2019) - Dupuis, Janae E.; Li, Jay; Callaghan, Brian C.; Reynolds, Evan L.; London, Zachary N.
ABSTRACT: Introduction: Nerve conduction studies are used to aid in the diagnosis of distal symmetric polyneuropathy (DSP). It is unclear whether bilateral lower extremity nerve conduction studies (NCS) are needed when evaluating for suspected DSP. Methods: We retrospectively analyzed NCS from patients who presented to the University of Michigan electromyography laboratory between July 1, 2016 and December 31, 2017 with symptoms of DSP to assess agreement and correlation between left and right lower extremity NCS parameters. Results: We found significant agreement between abnormalities in individual nerve parameters of the left and right lower extremities of 105 patients, most notably in the sural nerve. In the 53 patients with bilateral sural, peroneal, and tibial studies, there was also significant agreement between whether the left and right met electrodiagnostic criteria for DSP (κ = 0.77). Discussion: Bilateral lower extremity NCS may have limited utility in the evaluation of suspected DSP. Muscle Nerve, 2019